(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
During the pregnancy time most of the pregnancy women suffering with various disorders. On that polycystic ovary syndrome (PC0S) plays a major role. If a pregnant women having polycystic ovary syndrome (PCOS) it shows various pathophysiological changes in pregnant women. According to world health organization PCOS is the commonest cause of an ovulatory infertility